A copper-based catalyst for hydrogen production by electrolysis of water, its preparation method and application and a method for hydrogen production by electrolysis of water
Patent Information
- Application Number
- CN202611118284.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]在实际应用中,如果缺乏对表面微观相态和粗糙缺陷结构的精细控制,表面物相结构往往无法满足低电位下高效率产氢的需求
[0023]1、本申请的制备工艺极简高效,利于规模化生产。本发明巧妙地采用室温化学溶液(L-乳酸和碱液)浸泡的策略在纯铜箔表面原位溶出并重构形成一种特殊的粗糙缺陷结构。在电解测试中,特别是在-1.0 V vs. RHE的较低工作电位下,该特定表面可使电催化HER反应转化为绝对主导的目标反应,其氢气法拉第效率高度接近100%,成功实现了低能耗、高效率的电催化纯析氢。
Smart Images

Figure CN122898907A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical catalyst technology, specifically relating to a copper-based catalyst for hydrogen production by water electrolysis, its preparation method, and its application in the water electrolysis hydrogen production method. Background Technology
[0002] In water electrolysis for hydrogen production, the hydrogen evolution reaction (HER) is a core half-reaction and a crucial step in the production of high-purity hydrogen. Among numerous catalytic materials, copper-based materials, due to their unique electronic structure and low cost, have shown considerable potential for HER in electrocatalytic systems. Currently, researchers mainly optimize the catalytic performance of copper-based catalysts through strategies such as morphology control, defect engineering, and interface modification. In recent years, the regulation of surface physicochemical states has received significant attention in the field of catalytic materials. Through reasonable reconstruction of the surface microstructure, the adsorption and desorption behavior of reaction intermediates on the catalyst surface can be effectively optimized, demonstrating great potential for regulating HER activity.
[0003] Currently, commonly used copper-based catalyst surface modification strategies mainly rely on the cumbersome, demanding, and intricate construction of nanostructures (such as hydrothermal methods, high-temperature calcination, or using lattice mismatch to generate interfacial strain). These methods are extremely sensitive to synthesis conditions, have poor reproducibility in large-scale preparations, and are very expensive, which greatly limits their application in industrial scale-up. More importantly, existing surface modification methods often lack an effective means to directly construct highly active hydrogen evolution surfaces in situ through a simple, room-temperature wet chemical process.
[0004] In practical applications, without precise control over the surface micro-phase state and rough defect structure, the surface phase structure often cannot meet the requirements for high-efficiency hydrogen production at low potential.
[0005] Therefore, developing a simple and efficient surface reconstruction method to achieve customized design of catalyst surface structure through convenient process control and specifically activate hydrogen evolution pathways to obtain high-efficiency hydrogen production is a key problem that must be solved to promote the practical application of new high-efficiency water electrolysis hydrogen production materials.
[0006] To address the above problems, this invention is proposed. Summary of the Invention
[0007] The core of this invention lies in reconstructing a special rough defect surface in situ on the surface of a copper foil substrate through a simple and controllable room temperature oxidation method, thereby achieving efficient electrocatalysis of the HER pathway. The key technical point is the use of a specific immersion environment of a mixed solution of L-lactic acid and alkali to determine the microstructure and defect states of the surface.
[0008] The first aspect of this application provides a copper-based catalyst for hydrogen production by water electrolysis, wherein the copper-based catalyst is a copper foil with rough defects on its surface;
[0009] Alternatively, the copper-based catalyst may be a copper foil in which a densely stacked, uniform layer of nanoparticles is reconstructed in situ on the surface.
[0010] Preferably, the average particle size of the particles in the uniform nanoparticle layer is 22-26 nm.
[0011] A second aspect of this application provides a method for preparing a copper-based catalyst for hydrogen production by water electrolysis, the method comprising the following steps:
[0012] A mixed solution was prepared by mixing lactic acid and a strong base with water; the ratio of lactic acid, strong base, and water was 0.1 mol: 0.8 mol: 140 mL.
[0013] Then, the copper foil is immersed in the mixed solution for 5-15 minutes to obtain a copper foil with rough surface defects; the temperature of the mixed solution is 20-25 degrees Celsius.
[0014] Preferably, the copper foil with surface roughness defects is electrochemically reduced:
[0015] A three-electrode system was constructed in a potassium bicarbonate aqueous solution, with the copper foil having surface roughness defects selected as the working electrode.
[0016] Using cyclic voltammetry, with the voltage range set to -1.0 to -0.5 V, the scan rate set to 20-100 mV / s, and the number of scan cycles set to 10-30, a copper foil with a densely stacked uniform nanoparticle layer reconstructed in situ on the surface was obtained.
[0017] Preferably, the concentration of the potassium bicarbonate aqueous solution is 0.1-1 mol / L.
[0018] The third aspect of this application provides the application of the copper-based catalyst described in the first aspect for hydrogen production by water electrolysis.
[0019] Preferably, the working potential of the electrolyzed water is -1.0 V vs. RHE.
[0020] Preferably, the electrolyte for the electrolysis of water is a potassium bicarbonate aqueous solution with a concentration of 1-10M.
[0021] The fourth aspect of this application provides a method for producing hydrogen by electrolysis of water, using the copper-based catalyst described in any one of the first aspects as the working electrode, the electrolyte being a 0.1-1 mol / L potassium bicarbonate aqueous solution, and the working potential being -1.0 V.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The preparation process of this application is extremely simple and efficient, facilitating large-scale production. This invention ingeniously employs a room-temperature chemical solution (L-lactic acid and alkaline solution) immersion strategy to dissolve and reconstruct a unique rough defect structure in situ on the surface of pure copper foil. In electrolysis tests, particularly at the low operating potential of -1.0 V vs. RHE, this specific surface enables the electrocatalytic HER reaction to become the absolutely dominant target reaction, with a hydrogen Faraday efficiency approaching 100%, successfully achieving low-energy consumption and high-efficiency electrocatalytic pure hydrogen evolution.
[0024] 2. This application requires no complex nanostructures, no expensive noble metal doping, and even omits the in-situ electrochemical reduction step. Customized reconstruction of the catalyst surface structure can be achieved through extremely simple wet chemical adjustments, with mild conditions, short processing time, and excellent reproducibility, demonstrating extremely high potential for industrial scale-up applications.
[0025] 3. In the preferred technical solution, based on the above-mentioned room temperature chemical solution (L-lactic acid and alkaline solution) immersion scheme, in-situ electrochemical reduction is performed to reconstruct a densely stacked uniform nanoparticle layer on the copper foil surface. This material achieves a hydrogen Faraday efficiency of over 80% at a working potential of -1.0 V vs. RHE. Attached Figure Description
[0026] Figure 1 This is a SEM morphology characterization image of copper foil catalyst-1 in Example 1.
[0027] Figure 2 This is a SEM morphology characterization image of copper foil catalyst-2 in Example 2.
[0028] Figure 3 This is a SEM morphology characterization image of copper foil catalyst-3 in Example 3.
[0029] Figure 4 This is a SEM morphology characterization image of copper foil catalyst-4 in Example 4.
[0030] Figure 5 The image shows the Faraday efficiency of the copper foil catalyst-1 in Example 1 for the electrocatalytic reduction of carbon dioxide at different potentials.
[0031] Figure 6 This is a Faraday efficiency diagram of the electrocatalytic reduction of carbon dioxide products by copper foil catalyst-2 in Example 2 at different potentials.
[0032] Figure 7 The image shows the Faraday efficiency of the products of the electrocatalytic reduction of carbon dioxide at different potentials using copper foil catalyst-3 in Example 3.
[0033] Figure 8This is a Faraday efficiency diagram of the electrocatalytic reduction of carbon dioxide products at different potentials using copper foil catalyst-4 in Example 4.
[0034] Figure 9 The image shows the SEM morphology of copper foil catalyst-5 in Comparative Example 1.
[0035] Figure 10 The image shows the SEM morphology of copper foil catalyst-6 in Comparative Example 2.
[0036] Figure 11 The image shows the SEM morphology of copper foil catalyst-7 in Comparative Example 3.
[0037] Figure 12 The image shows the SEM morphology of copper foil catalyst-8 in Comparative Example 4.
[0038] Figure 13 The Faraday efficiency diagram for the electrocatalytic reduction of carbon dioxide products at different potentials is shown for Comparative Example 1, copper foil catalyst-5.
[0039] Figure 14 The Faraday efficiency diagram for the electrocatalytic reduction of carbon dioxide products at different potentials is shown for Comparative Example 2, copper foil catalyst-6.
[0040] Figure 15 The Faraday efficiency diagram for the electrocatalytic reduction of carbon dioxide products by copper foil catalyst-7 in Comparative Example 3 at different potentials is shown.
[0041] Figure 16 The Faraday efficiency diagram for the electrocatalytic reduction of carbon dioxide products at different potentials is shown for Comparative Example 4, copper foil catalyst-8. Detailed Implementation
[0042] The present invention will be described below with reference to specific embodiments, but the implementation of the present invention is not limited thereto. Experimental methods not specifically described in the embodiments generally use conventional conditions and conditions described in the manual, or conditions recommended by the manufacturer. The general equipment, materials, reagents, etc., used are all commercially available unless otherwise specified. The raw materials used in the following embodiments and comparative examples are all commercially available.
[0043] Example 1
[0044] A method for preparing a copper foil catalyst for water electrolysis with hydrogen evolution selectivity (copper foil catalyst-1) includes the following specific steps:
[0045] Step (1) Pretreatment of pure copper foil: 1×2.5 cm 2 Clean the copper foil thoroughly and set it aside.
[0046] Step (2) Oxidation: Add 40 mL of 2.6 M L-lactic acid aqueous solution and 32 g of sodium hydroxide to 100 mL of deionized water to prepare a mixed aqueous solution. Immerse the cleaned copper foil in this mixed aqueous solution for 10 minutes at room temperature (20 degrees Celsius).
[0047] Of course, since L-lactic acid and sodium hydroxide react, the above mixed aqueous solution can be regarded as a mixed solution of sodium lactate and sodium hydroxide.
[0048] Step (3) Electrochemical reduction: A three-electrode system was constructed in a 0.5 M potassium bicarbonate aqueous solution. The copper foil pretreated in step (2) was used as the working electrode, the carbon rod as the counter electrode, and the saturated calomel electrode as the reference electrode. Cyclic voltammetry was used with a voltage range of -1.0 to -0.5 V, a scan rate of 20 mV / s, and 20 scan cycles to perform electrochemical reduction treatment, thus obtaining copper foil catalyst-1.
[0049] The copper foil catalyst-1 described above was analyzed by scanning electron microscopy (SEM), and the results are as follows: Figure 1 As shown. Figure 1 As can be seen, a densely stacked uniform nanoparticle layer is reconstructed in situ on the surface of the copper foil, and the average particle size in the uniform nanoparticle layer is about 23.17±0.38 nm.
[0050] Example 2
[0051] A method for preparing a copper foil catalyst for water electrolysis with hydrogen evolution selectivity (copper foil catalyst-2) includes the following specific steps:
[0052] Step (1) Pretreatment of pure copper foil: 1×2.5 cm 2 Clean the copper foil thoroughly and set aside.
[0053] Step (2) Oxidation: Add 40 mL of 2.6 M L-lactic acid aqueous solution and 32 g of sodium hydroxide to 100 mL of deionized water to prepare a mixed aqueous solution. Immerse the cleaned copper foil in this mixed aqueous solution for 10 minutes.
[0054] Step (3) Electrochemical reduction: A three-electrode system was constructed in a 0.5 M potassium bicarbonate aqueous solution. The copper foil pretreated in step (2) was used as the working electrode, the carbon rod as the counter electrode, and the saturated calomel electrode as the reference electrode. Cyclic voltammetry was used with a voltage range of -1.0 to -0.5 V, a scan rate of 50 mV / s, and 20 scan cycles to perform electrochemical reduction treatment, thus obtaining copper foil catalyst-2.
[0055] The morphology of the above copper foil catalyst-2 was characterized by SEM results as follows: Figure 2As shown. Figure 2 As can be seen, the surface of the copper foil catalyst-2 exhibits a uniform and dense granular stacked morphology, which is a densely stacked uniform nanoparticle layer, and this uniform nanoparticle layer is formed through in-situ reconstruction on the copper foil surface. The average particle size of the nanoparticles is approximately 24.10 ± 0.52 nm.
[0056] Example 3
[0057] A method for preparing a copper foil catalyst for water electrolysis with hydrogen evolution selectivity (copper foil catalyst-3) includes the following specific steps:
[0058] Step (1) Pretreatment of pure copper foil: 1×2.5 cm 2 Clean the copper foil thoroughly and set aside.
[0059] Step (2) Oxidation: Add 40 mL of 2.6 M L-lactic acid aqueous solution and 32 g of sodium hydroxide to 100 mL of deionized water to prepare a mixed aqueous solution. Immerse the cleaned copper foil in this mixed aqueous solution for 10 minutes.
[0060] Step (3) Electrochemical reduction: A three-electrode system was constructed in a 0.5 M potassium bicarbonate aqueous solution. The copper foil pretreated by soaking in step (2) was used as the working electrode, the carbon rod as the counter electrode, and the saturated calomel electrode as the reference electrode. Cyclic voltammetry was used, with the voltage range set to -1.0 to -0.5 V, the scan rate set to 100 mV / s, and the number of scan cycles set to 20 cycles, to perform electrochemical reduction treatment, thus obtaining copper foil catalyst-3.
[0061] The morphology of the above copper foil catalyst-3 was characterized, and the SEM results are as follows: Figure 3 As shown. Figure 3 As can be seen, at a relatively fast in-situ reduction scanning rate, the material on the copper foil surface rapidly rearranges to obtain a densely stacked, uniform nanoparticle layer with an average particle size of 24.84 ± 0.30 nm. The average particle size on the copper foil in Example 3 is slightly larger than that in Examples 1-2.
[0062] Example 4
[0063] A method for preparing a copper foil catalyst for water electrolysis with hydrogen evolution selectivity (copper foil catalyst-4) includes the following specific steps:
[0064] Step (1) Pretreatment of pure copper foil: Clean 1×2.5 cm 2 Copper foil is available for use.
[0065] Step (2) Add 40 mL of 2.6 M L-lactic acid aqueous solution and 32 g of sodium hydroxide to 100 mL of deionized water to prepare a mixed aqueous solution. Soak the cleaned copper foil in this mixed aqueous solution for 10 minutes to obtain copper foil catalyst-4.
[0066] The morphology of the above copper foil catalyst-4 was characterized by SEM results as follows: Figure 4 As shown. Figure 4 It is evident that, without subsequent reduction treatment, due to the synergistic precipitation effect of strong alkali and lactic acid in the mixed solution, a coarse-particle stacked layer composed of large-sized non-metallic precursors is grown in situ on the surface of the copper foil.
[0067] Application examples
[0068] In a standard three-electrode testing system, a saturated calomel electrode or an Ag / AgCl electrode was used as the reference electrode, and a carbon rod as the counter electrode. The surface reconstruction catalysts (copper foil catalyst-1, copper foil catalyst-2, copper foil catalyst-3, and copper foil catalyst-4) obtained in Examples 1-4 were used as the working electrodes. A 0.5 M potassium bicarbonate aqueous solution was used as the electrolyte. Continuous water electrolysis and hydrogen evolution performance tests were conducted at a constant test potential gradient from -1.0 V to -1.6 V vs. RHE. The hydrogen products generated at the cathode were selectively and quantitatively analyzed using gas chromatography, and the corresponding Faraday efficiency (FE) was calculated.
[0069] Figure 5 The image shows the Faraday efficiency of the copper foil catalyst-1 in Example 1 for the electrocatalytic reduction of carbon dioxide at different potentials. Figure 6 This is a Faraday efficiency diagram of the electrocatalytic reduction of carbon dioxide products by copper foil catalyst-2 in Example 2 at different potentials. Figure 7 The image shows the Faraday efficiency of the products of the electrocatalytic reduction of carbon dioxide at different potentials using copper foil catalyst-3 in Example 3.
[0070] In potassium bicarbonate electrolyte systems, the cathode typically faces severe competition between the HER reaction and carbon-based reduction (producing CH4, C2H4, EtOH, etc.). The test results are analyzed below:
[0071] Figure 5-7 As can be seen, the morphology control and selectivity of Examples 1-3 are as follows:
[0072] The copper foil catalysts-1,-2, and-3 obtained in Examples 1-3 (constructing particle-reconstructed surfaces by adjusting cyclic voltammetric scan rates) exhibited hydrogen Faraday efficiencies of 83.7%, 80.8%, and 85.0%, respectively, at an operating potential of -1.0 V vs. RHE. These results demonstrate that optimizing the morphology of the dense nanoparticle layer on the surface by controlling the rearrangement rate during the electrochemical reduction process can, to some extent, regulate the hydrogen evolution selectivity and maintain a good level of hydrogen evolution catalysis.
[0073] Absolutely directional pure hydrogen evolution performance of Example 4:
[0074] Figure 8 This is a Faraday efficiency diagram of the electrocatalytic reduction of carbon dioxide products at different potentials using copper foil catalyst-4 in Example 4. Figure 8 As can be seen, the copper foil catalyst-4 prepared in Example 4 exhibits the most outstanding hydrogen evolution activity and extremely specific selectivity. At -1.0 V vs. RHE potential, its hydrogen Faraday efficiency reaches 99.9%. This indicates that, thanks to the active metal phase with a large electrochemical specific surface area and abundant intrinsic defects formed by the specific reconstruction of the copper foil surface, this catalyst can completely shield / suppress the carbon-based competitive reduction side reactions caused by bicarbonate ions in the electrolyte, making the electrocatalytic cathode reaction almost completely transformed into an absolutely dominant pure hydrogen evolution reaction. This achieves highly efficient and high-purity hydrogen production through water electrolysis in a complex system with extremely low energy consumption.
[0075] In the mixed oxidation preparation system of this invention (i.e., simultaneously containing L-lactic acid and basic components), whether or not in-situ electrochemical reduction is performed is a key "switch" for achieving customized control of surface morphology and hydrogen evolution selectivity. When the electrochemical reduction step is omitted (as in Example 4), the copper catalyst can retain the special defect phase formed by in-situ coordination and dissolution of the mixed oxidation liquid, thereby endowing it with an extremely pure hydrogen evolution selectivity of up to 99.9%, which is also a necessary prerequisite for avoiding the collapse of highly active surface structures. Conversely, when the electrochemical reduction step is introduced (as in Examples 1-3), the defect phase undergoes a reduction phase transition, transforming into a densely stacked layer of metal nanoparticles; at this time, although the hydrogen evolution Faraday efficiency drops back to the 80%–85% range, the surface particle size can be regularly and continuously finely adjusted by changing the reduction scan rate. Therefore, for the same mixed precursor system, omitting reduction is the core means of preserving absolute hydrogen evolution selectivity, while introducing reduction is an effective supplement to achieving a controllable morphology dimension.
[0076] Comparative Example 1
[0077] A method for preparing a comparative catalyst (copper foil catalyst-5) that is oxidized only by sodium hydroxide and not reduced:
[0078] Step (1) Pretreatment of pure copper foil: Clean 1×2.5 cm2 Copper foil is available for use.
[0079] Step (2) Oxidation: Add 32 g of sodium hydroxide to 100 mL of deionized water to prepare a sodium hydroxide solution, and denote this solution as the solution. Soak the cleaned copper foil in this solution for 10 minutes to obtain copper foil catalyst-5.
[0080] The SEM morphology characterization results of copper foil catalyst-5 in Comparative Example 1 are as follows: Figure 9 As shown. Figure 9 It is evident that, due to the complete absence of L-lactic acid coordination regulation in the oxidation solution, a single strong base only guides the formation of fine and dense conventional inactive oxide particles on the surface of the copper substrate.
[0081] Comparative Example 2
[0082] A method for preparing a comparative catalyst (copper foil catalyst-6) that is lactic acidified but not reduced:
[0083] Step (1) Pretreatment of pure copper foil: Clean 1×2.5 cm 2 Copper foil is available for use.
[0084] Step (2) Acidification: Add 40 mL of 2.6 M L-lactic acid to 100 mL of deionized water to prepare an acidic solution. Immerse the cleaned copper foil in this solution for 10 minutes, and then remove it to obtain copper foil catalyst-6.
[0085] The SEM morphology characterization results of copper foil catalyst-6 in Comparative Example 2 are as follows: Figure 10 As shown. Figure 10 It is evident that, due to the lack of synergistic precipitation effect of strong alkaline components, the single etching and dissolution of pure acidic solution results in a relatively smooth surface with a lack of precursor particle stacking.
[0086] Due to the lack of synergistic coordination with the strong base component, the etching with pure acid alone resulted in a chaotic stacking of large and highly uneven coarse particles on the copper surface. Compared to the previous example, the average particle size was significantly increased.
[0087] Comparative Example 3
[0088] A method for preparing a comparative catalyst (copper foil catalyst-7) that is only acidified with lactic acid and then reduced:
[0089] Step (1) Pretreatment of pure copper foil: Clean 1×2.5 cm 2 Copper foil is available for use.
[0090] Step (2) Acidification: Add 40 mL of 2.6 M L-lactic acid to 100 mL of deionized water to prepare a pure acidic solution. Soak the cleaned copper foil in this solution for 10 minutes.
[0091] Step (3) Electrochemical reduction: A three-electrode system was constructed, and the copper foil after soaking and pretreatment was selected as the working electrode. Cyclic voltammetry was used, with the voltage range set to -1.0 to -0.5 V, the scan rate set to 20 mV / s, and the number of scan cycles set to 20 cycles, thus obtaining copper foil catalyst-7.
[0092] The SEM morphology characterization results of copper foil catalyst-7 in Comparative Example 3 are as follows: Figure 11 As shown. Figure 11 It is evident that the pure acid etching in the early stage cannot form a thick precursor oxide particle layer. Combined with the subsequent electrochemical reduction phase transition, the copper surface undergoes further structural degradation, exhibiting an extremely smooth morphology with a severe lack of micro-roughness and undulating structure.
[0093] Comparative Example 4
[0094] A method for preparing a comparative catalyst (copper foil catalyst-8) that is oxidized and reduced only by sodium hydroxide:
[0095] Step (1) Pretreatment of pure copper foil: Clean 1×2.5 cm 2 Copper foil is available for use.
[0096] Step (2) Oxidation: Add 32 g of sodium hydroxide to 100 mL of deionized water to prepare a sodium hydroxide alkaline solution. Soak the cleaned copper foil in this solution for 10 minutes.
[0097] Step (3) Electrochemical reduction: A three-electrode system was constructed, and the soaked copper foil was selected as the working electrode. Cyclic voltammetry was used, with the voltage range set to -1.0 to -0.5 V, the scan rate set to 20 mV / s, and the number of scans set to 20, thus obtaining copper foil catalyst-8.
[0098] The SEM morphology characterization results of copper foil catalyst-8 in Comparative Example 4 are as follows: Figure 12 As shown. Figure 12 It is evident that the copper foil surface has a high degree of flatness, but it is locally scattered and aggregated with huge isolated clusters of phases caused by surface phase transitions, resulting in a significant reduction in the microscopic electrochemical active area.
[0099] Comparative Application Examples
[0100] In a standard three-electrode testing system, a saturated calomel electrode or an Ag / AgCl electrode was used as the reference electrode, and a carbon rod as the counter electrode. The surface reconstruction catalysts (copper foil catalyst-5, copper foil catalyst-6, copper foil catalyst-7, and copper foil catalyst-8) obtained in Comparative Examples 1-4 were used as the working electrodes. A 0.5 M potassium bicarbonate solution was used as the electrolyte. Continuous water electrolysis and hydrogen evolution performance tests were conducted under a constant test potential gradient from -1.0 V to -1.6 V vs. RHE. The hydrogen products generated at the cathode were selectively and quantitatively analyzed using gas chromatography, and the corresponding Faraday efficiency was calculated.
[0101] Figure 13 The Faraday efficiency diagram for the electrocatalytic reduction of carbon dioxide products at different potentials is shown for Comparative Example 1, copper foil catalyst-5. Figure 14 The Faraday efficiency diagram for the electrocatalytic reduction of carbon dioxide products at different potentials is shown for Comparative Example 2, copper foil catalyst-6. Figure 15 The Faraday efficiency diagram for the electrocatalytic reduction of carbon dioxide products by copper foil catalyst-7 in Comparative Example 3 at different potentials is shown. Figure 16 The Faraday efficiency diagram for the electrocatalytic reduction of carbon dioxide products at different potentials is shown for Comparative Example 4, copper foil catalyst-8.
[0102] Figure 13-16 As can be seen, at a potential of -1.0 V vs. RHE, the hydrogen selectivity of each comparison sample showed a significant decrease. The specific test results and scientific mechanism analysis are as follows:
[0103] Figure 13 As can be seen, the catalyst in Comparative Example 1 exhibits a hydrogen Faraday efficiency of only 65.8% at -1.0 V vs. RHE potential, accompanied by a large amount of carbon-based byproducts such as methane. This indicates that, due to the complete absence of L-lactic acid coordination regulation, the strong base only generates fine, dense, inactive oxide particles on the copper substrate surface. This structure cannot provide the active metal sites required for efficient hydrogen evolution, resulting in sluggish hydrogen evolution kinetics and a severe shift in the reaction pathway towards competing carbon-based side reactions.
[0104] Figure 14 As can be seen, the catalyst of Comparative Example 2 exhibits a hydrogen Faraday efficiency of only 71.2% at -1.0 V vs. RHE potential. This sample was etched and oxidized using only pure L-lactic acid, resulting in a smooth surface and a severe lack of precursor particle layer. During electrolysis testing, this smooth surface could not undergo the dramatic in-situ derivatization and reconstruction seen in Example 4, leading to a scarcity of effective catalytic active sites, a small electrochemical specific surface area, and an inability to dominate the reaction pathway, resulting in a significant loss of electrons to carbon-based parasitic reactions. This confirms that the coarse precursor layer synergistically constructed by the basic component and lactic acid is an indispensable prerequisite for achieving highly active in-situ reconstruction.
[0105] Figure 15 As can be seen, the catalyst of Comparative Example 3 exhibits a hydrogen Faraday efficiency of 75.7% at -1.0 V vs. RHE potential. This indicates that the sample underwent pure L-lactic acid etching and subsequent electrochemical reduction steps, but due to the lack of a strong base component in the precursor solution, the surface failed to accumulate a large number of coarse precursor particles as in Example 4. Cyclic voltammetric reduction of this surface lacking a precursor layer not only failed to produce drastic in-situ derivatization and reconstruction, but also led to further collapse of the substrate surface, resulting in an extremely smooth morphology. This extremely smooth surface severely lacks the active defect sites required for electrocatalytic hydrogen evolution, causing some electrons to be lost in the carbon reduction pathway, and the hydrogen evolution Faraday efficiency remains at a low level of 75.7%.
[0106] Figure 16 As can be seen, the catalyst in Comparative Example 4 exhibits a hydrogen Faraday efficiency as low as 57.4% at -1.0 V vs. RHE potential, indicating that a large number of electrons are consumed in the carbon reduction side reaction. This suggests that due to the absence of L-lactic acid interaction, the uncontrollable reduction following the combination of a single strong base leads to severe agglomeration of surface materials into large isolated clusters, drastically reducing the electrochemically active area and demonstrating the worst hydrogen evolution specificity among all samples.
[0107] The above comparative applications demonstrate that in carbon-rich electrolyte systems, the selectivity of hydrogen evolution at the cathode is highly dependent on the reconstruction pathway of the catalyst surface microstructure. Using L-lactic acid and alkaline solutions for surface oxidation reconstruction is a core technical characteristic that effectively avoids the collapse of surface active sites, successfully suppresses carbon-based parasitic side reactions, and ultimately constructs a catalyst with 99.9% ultra-high purity hydrogen evolution selectivity. Furthermore, based on the above, electrochemical reduction can be further performed. By controlling the rearrangement rate during the electrochemical reduction process to optimize the morphology of the dense nanoparticle layer on the surface, the hydrogen evolution selectivity can also be controlled to a certain extent, maintaining a good level of hydrogen evolution catalysis.
Claims
1. A copper-based catalyst for hydrogen production by water electrolysis, characterized in that, The copper-based catalyst is a copper foil with rough defects on its surface; Alternatively, the copper-based catalyst is a copper foil in which a densely stacked, uniform nanoparticle layer is reconstructed in situ on the surface. The average particle size in the uniform nanoparticle layer is 22-26 nm.
2. A method for preparing a copper-based catalyst for hydrogen production by water electrolysis, characterized in that, The preparation method includes the following steps: A mixed solution was prepared by mixing lactic acid and a strong base with water; the ratio of lactic acid, strong base and water was 0.1 mol: 0.8 mol: 140 mL. Then, the copper foil is immersed in the mixed solution for 5-15 minutes to obtain a copper foil with rough surface defects; the temperature of the mixed solution is 20-25 degrees Celsius.
3. The method for preparing the copper-based catalyst according to claim 2, characterized in that, The copper foil with rough surface defects was electrochemically reduced: A three-electrode system was constructed in a potassium bicarbonate aqueous solution. The copper foil with rough defects on its surface was selected as the working electrode. Cyclic voltammetry was used with a voltage range of -1.0 to -0.5 V, a scan rate of 20-100 mV / s, and a scan number of 10-30 cycles. This yielded a copper foil with a densely stacked uniform nanoparticle layer reconstructed in situ.
4. The method for preparing the copper-based catalyst according to claim 2, characterized in that, The concentration of the potassium bicarbonate aqueous solution is 0.1-1 mol / L.
5. The application of the copper-based catalyst according to claim 1 in the electrolysis of water to produce hydrogen.
6. The application according to claim 5, characterized in that, The working potential for the electrolysis of water is -1.0 V vs. RHE.
7. The application according to claim 6, characterized in that, The electrolyte for the electrolyzed water is a potassium bicarbonate aqueous solution with a concentration of 1-10M.
8. A method for producing hydrogen by electrolysis of water, characterized in that, The copper-based catalyst according to any one of claims 1-4 is used as the working electrode, the electrolyte is a 0.1-1 mol / L potassium bicarbonate aqueous solution, and the working potential is -1 V.